2015
DOI: 10.1371/journal.pone.0119776
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Methylenetetrahydrofolate Reductase Genotypes with the Risk of Childhood Leukemia in Taiwan

Abstract: BackgroundAcute lymphoblastic leukemia (ALL) is the most prevalent type of pediatric cancer, the causes of which are likely to involve an interaction between genetic and environmental factors. To evaluate the effects of the genotypic polymorphisms in methylenetetrahydrofolate reductase (MTHFR) on childhood ALL risk in Taiwan, two well-known polymorphic genotypes of MTHFR, C677T (rs1801133) and A1298C (rs1801131), were analyzed to examine the extent of their associations with childhood ALL susceptibility and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
6
23
0
Order By: Relevance
“…Genomic DNA from the peripheral blood leucocytes of each participant was prepared applying the QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan) and stored at -80˚C until processed as per our previous standard procedure ( [31][32][33]. The sequences of primers and the restriction enzymes for MMP-8 genotyping are designed by Terry Fox Cancer Research Lab and summarized in Table II.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA from the peripheral blood leucocytes of each participant was prepared applying the QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan) and stored at -80˚C until processed as per our previous standard procedure ( [31][32][33]. The sequences of primers and the restriction enzymes for MMP-8 genotyping are designed by Terry Fox Cancer Research Lab and summarized in Table II.…”
Section: Methodsmentioning
confidence: 99%
“…The genomic DNA from the peripheral blood leucocytes of each investigated subject was prepared applying the QIAamp Blood Mini Kit (Blossom, Taipei, Taiwan) and stored at −80˚C until processed as per our recent publications (25)(26)(27)(28). The sequences of primers and the restriction enzymes for MMP1 promoter 1607 genotyping are the same as our previous publication (29)(30)(31).…”
Section: Methodsmentioning
confidence: 99%
“…Pei et al (20) investigated the impact of two functional polymorphisms of FEN1 on the risk of childhood acute lymphoblastic leukemia (ALL). It was found that the AG and AA genotypes of the rs174538 variant, but not the rs4246215 variant, significantly decreased the risk of childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The gene is polymorphic and two functional variants, -69G>A (rs174538) and +4150G>T (rs4246215), have become points of interest. Previous studies have proposed that the two variants in FEN1 may function as biomarkers for BC, glioma, hepatocellular carcinoma, and esophageal, gastric, colorectal and lung cancer, as well as childhood leukemia (12,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%